Commercial Chicken Meat and Egg Production - Bell, Donald D.; Weaver, William D. (Boston, MA : Springer US, 2002)
Commercial Chicken Meat and Egg Production is the 5th edition of a highly successful book first authored by Dr. Mack O. North in 1972, updated in 1978 and 1984. The 4th edition was co-authored with Donald D. Bell in 1990. The book has achieved international success as a reference for students and commercial poultry and egg producers in every major poultry producing country in the world. The 5th edition is essential reading for students preparing to enter the poultry industry, for owners and managers of existing poultry companies and for scientists who need a major source of scientifically based material on poultry management. In earlier editions, the authors emphasized the chicken and its management. The 5th edition, with the emphasis shifted to the commercial business of managing poultry, contains over 75% new material. The contributions of 14 new authors make this new edition the most comprehensive such book available. Since extensive references are made to the international aspects of poultry management, all data are presented in both the Imperial and Metric form. Over 300 tables and 250 photos and figures support 62 chapters of text. New areas include processing of poultry and eggs with thorough discussions of food safety and further processing. The business of maintaining poultry is discussed in chapters on economics, model production firms, the use of computers, and record keeping. Updated topics include: breeders and hatchery operations; broiler and layer flock management; replacement programs and management of replacements; nutrition; and flock health. New chapters address flock behavior, ventilation, waste management, egg quality and egg breakage. Other new features include a list of more than 400 references and a Master List of the tables, figures, manufacturers of equipment and supplies, research institutions, books and periodicals, breeders, and trade associations. Commercial growers will find the tables of data of particular interest; scientists will be able to utilize the extensive references and to relate their areas of interest to the commercial industry's applications; and students will find that the division of the book into 11 distinct sections, with multiple chapters in each, will make the text especially useful.
Keywords: Chickens -- Handbooks, manuals, etc; Eggs -- Handbooks, manuals, etc; Handbooks and manuals